EVAPORATION TECHNIQUE OF ESSENTIAL OILS FOR IMPROVING OF IMMUNE RESPONSE OF BROILER CHICKENS - Waleed H. F.,; A. H. Ulaiwi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to investigate a new evaporation technique of essential oils; EOs (oregano, Lemongrass and bergamot essential oils) are in product called Fumite®Aroma. The study included 3 immunological parameters namely immunoglobulin A (IgA), interferon gamma (INF-γ), and newcastle disease (ND) antibody titer (Ab) as well as to compare between aerosol and ocular routes for ND vaccine. The study was designed as follow : {G1: is positive control given EOs(6g) only; G2: given Eos (6g) with ND vaccine by aerosol route; G3: given EOs (6g) with ND vaccine by ocular route; G4: given ND vaccine by aerosol route only; G5: given ND vaccine by ocular route only; G6: is negative control with no evaporation or vaccination}. Level of IgA at 16 days old there was a significant difference in G1 and G6 as compared with another groups. At 25 days old, G2, G3 and G5 revealed the highest levels as compared with another groups. At 34 days old, G3 was highest when compared to another groups. The results of IFN-γ showed at 16 days old showed a higher level in G3 as compared to another groups. the same in age 25 and 34.  Levels of ND titer at 16 and 25 days old showed that G3 were significantly highest as compared to another groups. At age 34 days, G3 and G2 showed the highest levels as compared to another groups. In conclusion EOs as evaporation. It can increase level of IgA, INF-γ and it improve immune response against ND.